2021
DOI: 10.1177/17470218211034130
|View full text |Cite
|
Sign up to set email alerts
|

Attention in post-lexical processes of utterance production: Dual-task cost in younger and older adults

Abstract: There is a general agreement that speaking requires attention at least for conceptual and lexical processes of utterance production. However, conflicting results have been obtained with dual-task paradigms using either repetition tasks or more generally tasks involving limited loading of lexical selection. This study aimed to investigate whether post-lexical processes recruit attentional resources. We used a new dual-task paradigm in a set of experiments where a continuous verbal production task involved eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…In contrast, DTC on RT was more severe when speech and Go tasks were simultaneously performed. These results are similar to performance patterns presented by healthy elderly on the same DT attributed to a shift of attentional focus between speech and visuo-motor task depending on visuo-motor task complexity level [15]. Such effect appears to be consistent with the capacity limit model [7] VF: Verbal Fluency.…”
Section: Dual-task Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, DTC on RT was more severe when speech and Go tasks were simultaneously performed. These results are similar to performance patterns presented by healthy elderly on the same DT attributed to a shift of attentional focus between speech and visuo-motor task depending on visuo-motor task complexity level [15]. Such effect appears to be consistent with the capacity limit model [7] VF: Verbal Fluency.…”
Section: Dual-task Performancesupporting
confidence: 86%
“…The index was reversed so that negative scores indicate a decreased performance. A detailed description of the DT can be found in Fournet et al [15].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have approached the question of what is shared between production and comprehension in a different way, by testing whether access to production and comprehension is possible at the same time, and testing whether there is interference between the tasks (e.g., Bürki et al, 2020;Fairs, 2019;Fairs et al, 2018;Fargier & Laganaro, 2016Fournet et al, 2021). In everyday life people tend to multitask quite often, such as driving while listening to the radio, or cooking while having a conversation, and we may feel less efficient or slowed down in one or the other activity.…”
Section: Simultaneous Production and Comprehension: Dual Task Paradigmsmentioning
confidence: 99%
“…Most of the identified research examined the relationship between attention/executive functioning and motor speech across 23 studies, revealing mixed evidence. Of 12 studies incorporating a dual-task paradigm, six reported significant declines in motor speech performance from single to dual-task conditions, including reduced speech rate (Kemper et al, 2003(Kemper et al, , 2005(Kemper et al, , 2009(Kemper et al, , 2011, word and syllable rate (Fournet et al, 2021), syllable accuracy, and speech duration (Whitfield & Goberman, 2017). These studies involved administering challenging secondary tasks including walking, ignoring speech or noise, digital tracking, and non-verbal cognitive tasks.…”
Section: Attention/executive Functionmentioning
confidence: 99%
“…To reduce potential confounding, Fournet et al (2021) measured word and syllable rate while participants recited the days of the week, a relatively automatic speech task.…”
Section: Attention/executive Functionmentioning
confidence: 99%